A matter of necessity? Enforced treatment under the Mental Health Act: R. (JB) v. responsible medical officer Dr A. Haddock, Mental Health Act Commission second opinion appointed doctor, Dr. Rigby, Mental Health Act Commission second opinion appointed Doctor Wood, [2006] E.W.C.A. Civ. 961 - Bartlett, Peter (Oxford University Press, 2007)
This case concerned the substantive prerequisites for involuntary treatment under the Mental Health Act 1983 (MHA). The parties agreed that following the European Court of Human Rights ruling in Herczegfalvy v. Austria, treatment for mental disorder could be enforced only if it were ‘medically necessary’.1 At the core of the decision in Haddock was how this phrase is to be construed. In particular, did Herczegfalvy require a two-part approach to the issue, first identifying with some certainty the disorder afflicting the patient and then determining whether the proposed treatment was necessary for that disorder, or could ‘medical necessity’ instead be determined as a single, multi-faceted question? Also at issue was the court's appropriate process and standard of review in such matters. Because of developments in the factual evidence and in the relevant case law during the litigation, a variety of other factors were considered, most particularly the relevance of a review tribunal's classification of mental disorder to the court's view of an individual's diagnosis.